JAKSA PENYIDIK DAN PENUNTUT UMUM DALAM PIDANA KORUPSI MENURUT HUKUM ACARA PIDANA INDONESIA (Faculty of Law, University of Palembang, 2023)
The purpose of the study was to determine the investigation process and the relationship between investigators and public prosecutors in the process of investigating criminal acts of corruption. This research is a normative legal research. By using secondary data consisting of primary legal materials, secondary legal materials including tertiary legal materials. The Criminal Justice System outlined by the Criminal Procedure Code is an integrated criminal justice system (SPP), so the role of the prosecutor in addition to being a public prosecutor as well as an investigator is not in accordance with the principles of the integrated criminal justice system. Therefore, in an integrated criminal justice system, there is mutual supervision among the components of the criminal justice system, especially those related to investigation and prosecution. This can be seen from the existence of a pretrial hearing regulated in Article 77 of the Criminal Procedure Code.Eradication of criminal acts of corruption is influenced by the work of the integrated criminal justice system (SPPT), the prosecutor's office has divided the powers of investigation and prosecution, but in practice it is still unclear how the horizontal supervision will be in the event of dual powers of prosecutors, investigators and public prosecutors in corruption crimes.